Using storybooks to enhance literacy development in early emergent readers: a closer look at the use of dialogic reading and concept of print development through print referencing - Peterson, Sarah (My University, 2014)
Kindergarten preparedness is commonly presumed to be an academic focus of preschool classrooms across the nation; however, an estimated one third of school-aged children entering kindergarten do not demonstrate skills commonly associated with adequate literacy development for this age group (Carnegie Foundation for the Advancement of Teaching, 1991). There exists an increasing amount of research data to suggest that storybook read alouds, using specific guidelines or strategies including dialogic reading, can increase student comprehension, aid in story retell, and advance critical thinking. In this study, the number of session participants ranged from one-on-one to small groups of 3-5 children. Data was collected for each session using videotapes which were then analyzed for visual cues that indicated student engagement, picture citations in retells and the number of words in a student response (directly related to the book). Data was also collected to determine how many questions the researcher was able to ask with reference to group size. Based on this research, students demonstrated an increased level of engagement, increasingly used pictures as clues during the retell process, and steadily increased the detailed length of responses as process repetition occurred.
Plan B Paper. 2014. Master of Science in Education- Reading--University of Wisconsin-River Falls. Teacher Education Department. 55 leaves. Includes bibliographical references (leaves 50-55).
Keywords: Language arts (Preschool)--Evaluation; Reading (Preschool); Literacy--Education (Preschool)--Evaluation